2020
DOI: 10.3390/ma13204478
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardant Properties and Thermal Decomposition Kinetics of Wood Treated with Boric Acid Modified Silica Sol

Abstract: This paper presents experimental research on the flame-retardant properties and thermal decomposition kinetics of wood treated by boric-acid-modified silica sol. The poplar wood was impregnated with pure silica sol and boric-acid-modified silica sol. The results showed that modifiers can be observed in the cell wall and cell lumen. The ignition time, second peak of the heat release rate, total heat release, and mass loss of the W-Si/B were delayed obviously. The composite silicon modification had a positive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In recent years, with the gradual development of the field of construction engineering, many researchers have devoted themselves to this field and developed a large number of flame-retardant polymer materials that can be used in construction engineering [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. According to the material composition, they can be divided into intrinsic-type and doped-type flame-retardant polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the gradual development of the field of construction engineering, many researchers have devoted themselves to this field and developed a large number of flame-retardant polymer materials that can be used in construction engineering [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. According to the material composition, they can be divided into intrinsic-type and doped-type flame-retardant polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Fire Performance Index (FPI) is the proportion of TTI and the maxima of the initial peak intensity of the heat release rate (HRR) curve. The larger the FPI, the better the flame retardant effect [21]. Combining the results of HRR, it can be concluded that FRB/APP has the best flame retardant effect in all combinations, and CFRB2 has the best flame retardant effect in composite combinations.…”
Section: Discussionmentioning
confidence: 82%
“…Classical approaches to wood FR have been widely studied, and pHRR reductions of more than 40% are now widespread. Wood has previously been vacuum pressure impregnated with clay [ 71 ], silica-based compounds [ 72 ], hydroxide-based compounds [ 73 ], and phosphorus-based compounds [ 74 ]. All of those treatments involve a reduced-pressure step to remove air from the wood and a high-pressure step where fire retardant substances are forced to impregnate the wood.…”
Section: Resultsmentioning
confidence: 99%